Microstructure and mechanical property degradation mechanism of Cu–Cr–Zr rail after extreme electromagnetic launches - Chengcheng Li; Weihao Li; Shiyu Hao; Huantong Shi; Li Chen; Chuncai Kong; Feng Jiang; Xingwen Li (Journal of Materials Research and Technology)
Clarifying the mechanical property degradation mechanism for the rail materials of the advanced electromagnetic launcher is vital for enhancing its life-cycle performance, which remains unclear so far. In this study, detailed analysis was performed on the Cu–Cr–Zr rail subjected to 12 launches to identify the key factors influencing the microstructures and mechanical properties. The results reveal significant decreases in the dislocation density and the precipitate size but not the content, and the almost unchanged grain size near the contact surface after the 12 shots. The hardness and yield strength of the rail surface decrease, especially in the middle section. Theoretical analysis proves the dominant role of the elevated temperature and the thermal phonon-dislocation interactions in reducing the dislocation activation energy and density, which lowers the diffusion coefficient and refines the precipitate by dissolution and re-precipitation induced by the extreme conditions. The calculated yield strength aligns well with the experimental data, confirming the lowered dislocation strengthening responsible for the decreased yield strength even with the increased grain boundary and precipitation strengthening.